Structure–Activity Relationship (SAR) Study of Spautin-1 to Entail the Discovery of Novel NEK4 Inhibitors - Mathias Elsocht (International Journal of Molecular Sciences, 2021)
Lung cancer is one of the most frequently diagnosed cancers accounting for the highest number of cancer-related deaths in the world. Despite significant progress including targeted therapies and immunotherapy, the treatment of advanced lung cancer remains challenging. Targeted therapies are highly efficacious at prolonging life, but not curative. In prior work we have identified Ubiquitin Specific Protease 13 (USP13) as a potential target to significantly enhance the efficacy of mutant EGFR inhibition. The current study aimed to develop lead molecules for the treatment of epidermal growth factor receptor (EGFR)-mutant non-small cell lung cancer (NSCLC) by developing potent USP13 inhibitors initially starting from Spautin-1, the only available USP13 inhibitor. A SAR study was performed which revealed that increasing the chain length between the secondary amine and phenyl group and introducing a halogen capable of inducing a halogen bond at position 4’ of the phenyl group, dramatically increased the activity. However, we could not confirm the binding between Spautin-1 (or its analogues) and USP13 using isothermal titration calorimetry (ITC) or thermal shift assay (TSA) but do not exclude binding under physiological conditions. Nevertheless, we found that the anti-proliferative activity displayed by Spautin-1 towards EGFR-mutant NSCLC cells in vitro was at least partially associated with kinase inhibition. In this work, we present N-[2-(substituted-phenyl)ethyl]-6-fluoro-4-quinazolinamines as promising lead compounds for the treatment of NSCLC. These analogues are significantly more effective towards EGFR-mutant NSCLC cells than Spautin-1 and act as potent never in mitosis A related kinase 4 (NEK4) inhibitors (IC50~1 µM) with moderate selectivity over other kinases.